A common pronociceptive pain modulation profile typifying subgroups of chronic pelvic pain syndromes is interrelated with enhanced clinical pain. Issue 6 (June 2017) - Grinberg, Keren; Granot, Michal; Lowenstein, Lior; Abramov, Liora; Weissman-Fogel, Irit
Abstract : Abstract: Provoked vestibulodynia (PVD) and painful bladder syndrome (PBS), subgroups of chronic pelvic pain syndromes (CPPS), are considered to share common biophysiological peripheral mechanisms. In addition, indications of a pronociceptive pain profile coexisting with psychological vulnerability suggest common dysfunctional pain processing and pain modulation in these 2 subgroups of CPPS. We therefore aimed at comparing the pain profile and psychological traits of patients with PVD and PBS to see whether the pain profile contributes to intersubject variability of clinical pain symptoms. Patients with PVD (n = 18) and PBS (n = 21) were compared with healthy controls (n = 20) in their responses to (1) pain psychophysical tests applied to both referred (suprapubis) and remote (hand) body areas and (2) pain-related psychological factors (pain catastrophizing, depression, anxiety, and somatization). We found a similar pronociceptive pain profile in the 2 subgroups of CPPS—enhanced facilitation (ie, hyperalgesia in the referred body area [ P < 0.001]) and inefficient inhibition (ie, reduced conditioned pain modulation [ P < 0.001] that were associated with both enhanced pain ratings evoked during trigger point examination [ P < 0.037]) and higher Brief Pain Inventory ratings ( P = 0.002). The latter was also correlated with pain catastrophizing ( r = 0.504, P = 0.001) and depression symptoms ( r = 0.361, P = 0.024). The findings suggest common mechanisms underlying a dysfunctional nociceptive system in both PVD and PBS. The intersubject variability in the level of dysfunction and its association with disease severity recommends a personalized pain treatment that may alleviate daily pain and dysfunction in patients with CPPS. Abstract : The pain modulation profile in both painful bladder syndrome and provoked vestibulodynia patients with chronic pelvic pain, with enhanced facilitatory and inefficient inhibitory processes, suggests a common pronociceptive mechanism.